Drying of black pepper (Piper nigrum L.) using solar tunnel dryer - Joy, C. M.; Pittappillil, George Peter; Jose, K. P. (Universiti Putra Malaysia Press, 2002)
Black pepper (Piper nigrum L.) is considered to be the king among the spices. The State of Kerala alone contributes about 97% to the total pepper production in India. Seventy-five pepper varieties are cultivated in different parts of the country. Pungency and aroma are the most important qualities o fpepper, which is attributed to oleoresin and volatile oil respedively. The quality of pepper is very much dependent on the post-harvest methods. An extensive survey on the occurrence of the black pepper and drying methods were conducted in this investigation. Only conventional open sun drying is practised in the State of Kerala. Pepper samples colleded from different locations were dried in an imported tunnel dryer (Germany) and quality of the tunnel-dried spice was compared with commercial samples. Blanching was done before each drying. ASTA (American Spice Trade Association) and Agmark quality standards were tested on the tunnel dried and commercial samples. Significant variations of pepper quality between sampling stations were noticed. Approximately 6 days were taken for the drying of commercial samples whereas in solar tunnel dryer it took only 8 hours. Piperine content in commercial samples was only 4% l7y weight while in dryer samples it was 4.5% l7y weight. Tunnel dried samples had better physical quality than the commercial samples as specified l7y ASTA. Quality improvement and redudion in drying time were evident for the solar tunnel dried samples. Solar tunnel dryer imported from Germany is highly suitable for black pepper drying. optimum conditions required for the drying of this spice could be defined. Physico-chemical quality analyses proved that the dryer tested for the pepper drying is efficient enough to produce pepper of export quality.